ANALISIS INVESTASI DENGANPERHITUNGAN NPV, IRRDAN PAYBACK PERIOD PADA PRODUKSI IKAN PRESTO GITA PINDANG DESA KALITENGAH KECAMATAN GOMBONG - Ediwodjojo, Sotya Partiwi; Ginting, Ika Raniya (ANALISIS FAKTOR-FAKTOR PENYEBAB TERJADINYA KREDIT MACET PADA KUD RAHMAT WIDODO KECAMATAN SRUWENG KABUPATEN KEBUMEN, 2018)
The production of Milk Fish Gita Pindang have not yet a recording of budgeting system data.To recognite the feasibility of investment and in this research was focused to calculation of NPV, IRR and Payback Period.Data collection methods used interview method, observation and documentation. The arranging used was descriptive quantitative methods and based on the carculation of NPV, IRR, and Payback Period.          The result of analysis calculation, NPV, IRR and Payback Period on Milk Fish Production Gita Pindang, obtained result for NPV equal to Rp -3.981.277,00. So for H1 which state if the calculation of NPV is greater than zero or NPV in economic age yields positive value, otherwise H1 is rejected because of negative NPV result. For the carculation of IRR is obtained at 5%, so for H2 which state if the carculation of IRR produces a large discount rate, otherwise H2 is rejected because the result of carculation IRR small than the expected profit. Payback period calculation result, obtained for 4 years 3 months 12 days, then for H3 accepted because the payback period result faster than the economic age.